Risky injection practices and HCV awareness in Chiang Mai Province, Thailand: a respondent-driven sampling study of people who inject drugs - Myrtille Prouté (2020)
BACKGROUND: People who inject drugs (PWID) are the most exposed to hepatitis C virus (HCV). In Thailand, drug use is highly criminalized, and harm reduction services are scarce. This study estimates risky injection practices and assesses the proportion of HCV awareness and screening in the PWID population in Northern Thailand. METHODS: We used respondent-driven sampling (RDS) to recruit PWID in Chiang Mai Province. Social and behavioural data were collected through face-to-face interviews at an addiction treatment facility. Weighted population estimates were calculated to limit biases related to the non-random sampling method. Univariate and multivariate analyses were performed to study factors associated with HCV awareness and screening. RESULTS: One hundred seventy-one PWID were recruited between April 2016 and January 2017. Median age was 33 (Interquartile range: 26-40) years, 12.2% were women, and 49.4% belonged to a minority ethnic group. Among participants, 76.8% injected heroin, 20.7% methadone, and 20.7% methamphetamine. We estimate that 22.1% [95% CI: 15.7-28.6] of the population had shared needles in the last 6 months and that 32.0% [95% CI: 23.6-40.4] had shared injection material. Only 26.6% [95% CI: 17.6-35.6] had heard of HCV. Factors independently associated with knowledge of HCV included belonging to a harm reduction organization (adjusted odds ratio (aOR) = 5.5 [95% CI: 2.0-15.3]) and voluntary participation in a drug rehabilitation programme (aOR = 4.3 [95% CI: 1.3-13.9]), while Lahu ethnicity was negatively associated (aOR = 0.3 [95% CI: 0.1-0.9]). We estimate that 5% of the PWID population were screened for HCV; the only factor independently associated with being screened was membership of a harm reduction organization (aOR = 5.7 [95% CI: 1.6-19.9]). CONCLUSION: Our study reveals that the PWID population is poorly informed and rarely screened for HCV, despite widespread risky injection practices. A public health approach aimed at reducing the incidence of HCV should target the PWID population and combine harm reduction measures with information and destigmatization campaigns. Civil society organizations working with PWID are a major asset for the success of such an approach, based on their current positive interventions promoting awareness of and screening for HCV.